2021
DOI: 10.1007/s40766-021-00027-6
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational imaging for label-free cancer diagnosis and classification

Abstract: The first key step in the detection and classification of most cancers is the microscopic assessment of thin tissue slices, the so-called "histopathology". This procedure is still nowadays, similarly to 150 years ago, performed by staining the tissue with two or more dyes able to bind to specific biological structures, followed by visual inspection by the histopathologist under the bright-field optical microscope. This approach involves long manual procedures which can be accompanied by human errors, subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 232 publications
(322 reference statements)
0
17
0
Order By: Relevance
“…Finally, we demonstrated that our technique can be used to identify the tumor regions and differentiate them from the healthy portions in thin tissue slides. 1 , 33 , 56 58 Nowadays, the identification of cancer and the corresponding changes in the tissue morphology is based on staining techniques. The most common one is H&E, which employs the dyes hematoxylin (marking the nuclei in purple/blue) and eosin (providing a pink color to the cytoplasm and the extracellular connective tissue matrix).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we demonstrated that our technique can be used to identify the tumor regions and differentiate them from the healthy portions in thin tissue slides. 1 , 33 , 56 58 Nowadays, the identification of cancer and the corresponding changes in the tissue morphology is based on staining techniques. The most common one is H&E, which employs the dyes hematoxylin (marking the nuclei in purple/blue) and eosin (providing a pink color to the cytoplasm and the extracellular connective tissue matrix).…”
Section: Resultsmentioning
confidence: 99%
“…Vibrational microscopy is a powerful investigation tool in life sciences, as it delivers vibrational maps of unstained tissues and cells, providing high chemical specificity in a label-free and nondestructive manner. Among vibrational microscopy techniques, coherent anti-Stokes Raman scattering (CARS) has gained prominence, since it enables high-speed imaging thanks to the nonlinear nature of the optical processes occurring at the sample under tight-focusing conditions. With respect to spontaneous Raman (SR), in which a monochromatic excitation beam interacts with thermal vibrations, in CARS two synchronized, spatially overlapped and frequency detuned pulses, the pump (at frequency ω p ) and the Stokes (at frequency ω S ), generate a vibrational coherence at the frequency Ω = ω p – ω S .…”
Section: Introductionmentioning
confidence: 99%
“…The low sensitivity arises because the Raman scattering process has extremely low probability, which we compensated by long exposure times (~10mins per cell). Future studies that require lower LODs or faster scanning could adopt advanced Raman techniques such as stimulated Raman spectroscopy (SRS) 63 , coherent anti-Stokes Raman spectroscopy (CARS) 64 or surface-enhanced Raman spectroscopy (SERS) [65][66][67][68] , which provide resonant signal-enhancements and fluorescence-background suppression. 69 Additionally, while the 1401 cm -1 peak can be distinguished, it sits on the shoulder of an adjacent peak at 1445 cm -1 , associated with CH2 mode in DNA, making quantification challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Raman microscopy is a powerful tool for the investigation of life sciences as it provides chemical maps of cells and tissue in a label-free and non-invasive manner 1 . Despite its high specificity and sensitivity, spontaneous Raman (SR) scattering features a small Raman cross-section preventing high-speed imaging.…”
Section: Introductionmentioning
confidence: 99%